The Acadian Flycatcher is a habitat specialist, and it shows - Nicole L Regimbal; Shelby H Riskin (Avian Conservation and Ecology)
Declines in North American bird populations are being driven by a suite of threats, and it can be difficult to disentangle drivers of decline for any single species, especially those with large ranges or that experience different threats in different parts of their range. Community science platforms offer new and rapidly expanding datasets to observe species across space and time. Here, we use community science databases to analyze the habitat characteristics of the Acadian Flycatcher ( Empidonax virescens ), a Neotropical migrant songbird that is threatened across portions of its range. The Acadian Flycatcher is often described as a habitat specialist, though often only where it is considered at risk. We use Acadian Flycatcher observations sourced from one of the biggest community science platforms, eBird, and assess habitat land cover and co-occurrence of species associated with habitat quality for each of these observations. We use publicly available land use data to assess habitat cover and assess co-occurring species using observations sourced from multiple community science platforms. Our results show the Acadian Flycatcher is largely observed in high-quality landscapes of preferred habitat (31% deciduous forest and 11% wetland cover) and without invasive vegetation more than bird observation sites where the Acadian Flycatcher was not detected (25% more likely to be near preferred trees, 77% less likely to be near invasive vegetation, p < 0.001). Our results also show an overrepresentation of urban land cover, potentially highlighting a bias in some community science data due to observer behavior. Overall, our results support land management strategies that maintain patches of native land cover and manage invasive species and highlight how community science databases can provide important information about species’ presence over space and time.